2021
DOI: 10.1037/adb0000712
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Reward Probability Index in emerging adult drinkers.

Abstract: Objective: Diminished access to environmental rewards is an established risk factor for addiction and a focus of many effective treatment approaches. Nevertheless, there is inconsistency in measurement approaches and a need for a psychometrically sound measure. The Reward Probability Index (RPI; Carvalho, Behavior Therapy, 42, 2011, pp. 249–262) is a 20-item self-report rating scale that measures access to and ability to experience psychosocial reward. Method: The current studies sought to evaluate the psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Both subscales are scored such that higher scores indicate higher levels of reward obtained. Psychometric evaluations of the RPI have been conducted with emerging adult samples and have demonstrated evidence of reliability for both subscales as well as convergent validity with measures of activity and avoidance, environmental reward, and depression (Carvalho et al., 2011; Voss et al., 2021). In the present sample, Cronbach's alpha values for the Reward Probability and Environmental Suppressors subscales were .78 and .68, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Both subscales are scored such that higher scores indicate higher levels of reward obtained. Psychometric evaluations of the RPI have been conducted with emerging adult samples and have demonstrated evidence of reliability for both subscales as well as convergent validity with measures of activity and avoidance, environmental reward, and depression (Carvalho et al., 2011; Voss et al., 2021). In the present sample, Cronbach's alpha values for the Reward Probability and Environmental Suppressors subscales were .78 and .68, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Aversive experience was assessed with the Reward Probability Index (RPI; Carvalho et al, 2011 ), which comprises of 20 items divided into two subscales. The 9-item Environmental Suppressors subscale (hereafter “aversive experience”) measures aversive experiences (α = 0.82), with the strongest loaded items in the cited factor analysis being “I have had many unpleasant experiences” and “It seems like bad things always happen to me.” The Reward Probability subscale (hereafter “reward probability”) measures the ability to obtain/experience reward (α = 0.82), with the strongest loaded items being “I have the abilities to obtain pleasure in life” and “I feel a strong sense of achievement.” Participants endorsed each item on a scale ranging from 1 “ Strongly disagree ” to 4 “ Strongly agree .” The validity of the Environmental Suppressors subscale measure of aversive experience for the current analytical purposes is supported by its unique association with adverse childhood experiences and with income and alcohol dependence (controlling for consumption) over the Reward Probability subscale ( Loomis, 2020 ; Voss et al, 2021 ).…”
Section: Methodsmentioning
confidence: 97%
“…Participants endorsed each item on a scale ranging from 1 "Strongly disagree" to 4 "Strongly agree." The validity of the Environmental Suppressors subscale measure of aversive experience for the current analytical purposes is supported by its unique association with adverse childhood experiences and with income and alcohol dependence (controlling for consumption) over the Reward Probability subscale (Loomis, 2020;Voss et al, 2021).…”
Section: Questionnairesmentioning
confidence: 99%
“…The results reported by Murphy et al using the 20‐item RPI and the consistency of results obtained with those reported previously in studies using the PES are very encouraging in terms of potential to reinvigorate this vital area of research. I know the cumbersome nature of the PES‐suppressed inclusion of that instrument in studies conducted in my research group, a trend that I plan to change based on the excellent work reported by Murphy and colleagues, work that includes ongoing psychometric improvements to the RPI in the study of substance use (Voss et al, 2021). Of course, the excellent seminal work of Carvalho et al (2011) in surmounting the limitations of the PES with development of the RPI warrants acknowledgment as well.…”
Section: Salient Contributionsmentioning
confidence: 99%